An OGT-STAT5 Axis in Regulatory T Cells Controls Energy and Iron Metabolism - Zhang, Zengdi; Salgado, Oscar C.; Liu, Bing; Moazzami, Zahra; Hogquist, Kristin A.; Farrar, Michael A.; Ruan, Hai-Bin (Frontiers in Immunology, 2022)
The immunosuppressive regulatory T (Treg) cells exert emerging effects on adipose tissue homeostasis and systemic metabolism. However, the metabolic regulation and effector mechanisms of Treg cells in coping with obesogenic insults are not fully understood. We have previously established an indispensable role of the O-linked N-Acetylglucosamine (O-GlcNAc) signaling in maintaining Treg cell identity and promoting Treg suppressor function, via STAT5 O-GlcNAcylation and activation. Here, we investigate the O-GlcNAc transferase (OGT)-STAT5 axis in driving the immunomodulatory function of Treg cells for metabolic homeostasis. Treg cell-specific OGT deficiency renders mice more vulnerable to high-fat diet (HFD)-induced adiposity and insulin resistance. Conversely, constitutive STAT5 activation in Treg cells confers protection against adipose tissue expansion and abnormal glucose metabolism upon HFD feeding, in part by suppressing adipose lipid uptake and redistributing systemic iron storage. Treg cell function can be augmented by targeting the OGT-STAT5 axis to combat obesity and related metabolic disorders.